Seroprevalence for brucellosis and leptospirosis in dogs from Belem and Castanhal, State of Para, Brazil - Paz, Giselle Souza da [UNESP]; Rocha, Katarine de Souza; Lima, Michele de Souza; Jorge, Ediene Moura; Figueiredo Pantoja, Jose Carlos [UNESP]; Guimaraes de Moraes, Carla Cristina; Langoni, Helio [UNESP] (Inst Nacional Pesquisas Amazonia, 2015)
Brucellosis and leptospirosis are widely spread bacterial infections and dogs are the most important source of infection and reservoir for diseases. Dogs can disseminate the agents in the environment and transmit them to humans and/or other animals. The objective of this study was assess the occurrence of reactive to antibodies anti-Leptospira spp., Brucella canis and B. abortus in Belem and Castanhal, State of Para, Amazon, Brazil. A total of 156 samples were randomly collected in the city of Belem and 158 samples in Castanhal. The anti-B. canis antibodies research was performed by Agar Gel Immunodiffusion (AGID) with and without 2-mercaptoethanol serum treatment (AGID-2ME). To assess the anti-B. abortus antibodies, the technique of Fast Seroagglutination with buffered acidified plate antigen (BAPAT) was used. For anti-Leptospira spp. antibodies research, the Microscopic Agglutination Technique (MAT) was used. No animal reacted to Brucella abortus and one animal was reactive to B. canis at the AGID, but it was negative to the AGID-2ME test. Seventeen percent of dogs (47/274) presented anti-Leptospira spp. antibodies, with prevalence of serovar Canicola. The dogs from Belem and Castanhal are not source of infection for B. abortus and B. canis, however, they are reservoirs for different serovars of Leptospira spp.
Keywords: Leptospira spp.; Brucella spp.; domestic canids; Serology